2018
DOI: 10.3390/nu10111730
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intakes and Food Sources of Filipino Infants, Toddlers and Young Children are Inadequate: Findings from the National Nutrition Survey 2013

Abstract: Comprehensive assessment of nutrient intakes and food sources of nutrients in Filipino children under 5 years old are lacking. We studied energy and nutrient intakes and food sources in 4218 children aged 6–59.9 months using two 24-h dietary recalls. Usual energy and nutrient intakes were estimated using the PC-SIDE program. Reported foods and beverages were assigned to one of 85 food groups. Percentage contribution of each food group to nutrient intake was calculated. The results showed that the intake of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 20 publications
4
65
0
Order By: Relevance
“…This is similar to results reported in other countries including India, China and Japan [22][23][24]. Forti ed young child beverages provide a source of iron among Filipino infants (6-11.9mo) and toddlers (12-23.9mo), respectively [5]. However, consumption of these products was more prevalent in infants and toddlers from higher income households.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is similar to results reported in other countries including India, China and Japan [22][23][24]. Forti ed young child beverages provide a source of iron among Filipino infants (6-11.9mo) and toddlers (12-23.9mo), respectively [5]. However, consumption of these products was more prevalent in infants and toddlers from higher income households.…”
Section: Discussionsupporting
confidence: 87%
“…This was re ected by poorer intakes of vitamins and minerals in toddlers from poorer backgrounds. However, a recent paper by Denney et al in the same population, identi ed inadequate of protein and B vitamins in Filipino infants and toddlers at population level [5]. Ideally, the mandatory rice with vitamins and minerals in the Philippines could provide a public health opportunity to improve nutrient intakes, particularly among children from poorer households.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children require sufficient nutrients to meet the need for rapid growth and development [2]. Many studies around the world focus on evaluating nutrient intakes and their adherence to recommended reference values among young children [3][4][5][6]. Bailey et al [3] reported that 79% and 30% of 3-4-year-old US children consumed less than the estimated average requirement (EAR) for vitamins D and E, respectively, although their intakes of most other nutrients were largely adequate.…”
Section: Introductionmentioning
confidence: 99%